Regions and the world economy : the coming shape of global production, competition, and political order - Scott, Allen J., (Allen John), 1938- (Oxford University Press, 1998)
As we enter the twenty-first century, one of the dramatic shifts in the world system is the increasing openness and interpenetration of national economies and sovereign states. This shift is associated on the one hand with the beginnings of a progressive transfer of certain economic and political functions upward to the pluri-national and global levels; and on the other hand with a countervailing trend to the reinforcement of economic and political life at the sub national, regional level. This book is a wide-ranging exploration of the economic logic and political meaning of these developments, with special reference to a reconceptualisation of the economic geography of the modern world as an emerging global mosaic of regional systems of production and exchange. The steady globalisation of economic activity over the last few decades has intensified the re-assertion of the region as a critical locus of economic order and as a potent foundation of competitive advantage. As a corollary, many regions in the modern world are also beginning to acquire an intense self-consciousness of themselves as socio-political and economic entities, and all the more so as they increasingly find themselves bound together in both competitive and collaborative relationships across national borders. The significance of these tendencies for new kinds of political mobilisation is explored, and their potential impacts of substantive forms of democracy and citizenship in the new world order are assessed.